4CPS-141 Pharmaceutical interventions in a medical emergency department: 6-months experience. Issue 1 (23rd March 2023) - El Qabissi, O; Lasri, FZ; Daoudi, H; Chaibi, A; Ait el Cadi, M
Abstract : Background and Importance: Medication errors are a major global public health problem that requires a very important approach and collaborative work between physicians, pharmacists and nurses. Pharmaceutical interventions (PI) are an effective way to fight drug iatrogeny. Aim and Objectives: The objective of the study was to analyse pharmaceutical interventions and their impact on patients hospitalised in a medical emergency department Material and Methods: This is a retrospective study conducted in a medical emergency department of the Ibn Sina Hospital in Rabat over a period of 6 months. Prescriptions were analysed and validated according to the methodology of the French Society of Clinical Pharmacy (SFPC). The relevance of the PIs was assessed by their acceptance rate by the prescribers and their clinical impact was evaluated according to the Hatoum scale. Results: A total of 158 Pharmaceutical interventions were recorded over six months. Of these, 98% were accepted by the prescriber. The sex ratio (male/female) was 1.35. The average age of our patients was 56.06 ± 15.81 years. 86 PIs (55%) concerned an antibiotic. The main prescription problems were overdose (29%). Our interventions concerned dosage adjustment (32.27%), optimisation of administration modalities (22.15%). Conclusion and Relevance: This study highlights the importance of the clinical pharmacist in the fight against drug iatrogeny. References: Hedira et al . Évaluation de l'activité de pharmacie clinique dans un centre hospitalier mère-enfant en Tunisie – 53- Le Pharmacien Hospitalier et Clinicien. 2018 A. Clementz et al . Mise en place et évaluation des validations d'ordonnances et d'interventions pharmaceutiques dans un service d'urgences adultes. Le Pharmacien Hospitalier et Clinicien, Juin 2017; 52 : e47–e53 Abdelaziz H et al . Impact des services de pharmacie clinique dans une unité de court séjour d'un service d'urgence hospitalier au Qatar. Int J Clin Pharm 2016;38 :776–9 Nielsen T et al . Service de pharmacien clinicien dans le service aigu. Int J Clin Pharm 2013;35 :1137–51. Conflict of Interest: No conflict of interest